1999
DOI: 10.1046/j.1365-2648.1999.01002.x
|View full text |Cite
|
Sign up to set email alerts
|

Medication management: an exploratory study into the role of community mental health nurses

Abstract: The recent emphasis on community care for those with mental illness has changed working patterns and modified inter-professional role boundaries within multi-disciplinary teams. Clients with serious mental illness are usually prescribed medications, which have a wide range of side effects. However, it is uncertain who is responsible for monitoring clients for the side effects of their medications, ensuring clients' and carers' understandings of their prescribed medications and optimizing compliance with medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 82 publications
2
72
0
Order By: Relevance
“…Francis Report, Recommendation 94) [59]. Before undertaking larger studies, we tested the feasibility and clinical impact of our approach to the “ADR problem” [6064]. Objectives of this pilot were to appraise the logistics of (1) recruitment, retention, and implementation and (2) assessment of clinical benefits of the profile for people with dementia prescribed antipsychotic, antidepressant or antiepileptic medication.…”
Section: Introductionmentioning
confidence: 99%
“…Francis Report, Recommendation 94) [59]. Before undertaking larger studies, we tested the feasibility and clinical impact of our approach to the “ADR problem” [6064]. Objectives of this pilot were to appraise the logistics of (1) recruitment, retention, and implementation and (2) assessment of clinical benefits of the profile for people with dementia prescribed antipsychotic, antidepressant or antiepileptic medication.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the nurse must exercise judgment as to when to enlist the intervention of specialist medical staff (Jordan et al, 1999). This exercise of judgment is particularly apparent in rural and remote areas where full time psychiatrists are frequently not available and the primary monitoring of psychiatric treatment is often undertaken by general practitioners (GPs).…”
mentioning
confidence: 99%
“…In an exploratory study into the role of community mental health nurses, Jordan et al (1999) found that nurses are expected to manage and monitor medications accurately and adequately, are responsible for assessing any contraindications, recognizing and assessing side effects, and treatment responses. Marland (1999) looked carefully at the question of depot medication and medication compliance.…”
Section: Importance Of Medication Managementmentioning
confidence: 99%